The Therapeutic Potential of Cola nitida in Health and Disease: A Review - Sanusi, Kamaldeen Olalekan; Usman, Umar Zayyanu; Usman, Dawoud; Adeshina, Kehinde Ahmad; Uthman, Yaaqub Abiodun; Jimoh, Lukman; Imam-Fulani, Aminat Omolola (Biology, Medicine, & Natural Product Chemistry, 2023)
Cola nitida, also known as Kola nut, is a tropical plant native to West Africa and has a rich history of traditional medicinal use. In this narrative review, we aim to provide an overview of the protective effects of Cola nitida in various health and disease states. Cola nitida has been traditionally used for its medicinal properties, and its bioactive compounds include caffeine, alkaloids, tannins, flavonoids, and phenolics. These compounds contribute to its potential therapeutic effects. Here, we examine the potential benefits of Cola nitida in several areas of health, discussing its role in cognitive function, cardiovascular health, immune system function, gastrointestinal health, and metabolic and endocrine health. Relevant original articles available from PubMed, African Journals Online (AJOL), SCOPUS, and Google Scholar were retrieved using the keywords â€œcolaâ€ AND â€œnitidaâ€ without date restriction until July 17, 2023. Evidence suggests that Cola nitida may have positive effects on health, with indications of adverse effects only from its chronic usage. However, more research is needed to establish its efficacy and safety. Cola nitida holds promise as a natural remedy for various health conditions. Understanding the benefits and limitations of Cola nitida will contribute to its effective utilization in health and disease management.